Not all personal definitions of healthy eating are linked to orthorexic behaviors among French college women. A cluster analysis study. (1st July 2021) - Yakın, Ecem; Raynal, Patrick; Chabrol, Henri
Abstract: Purpose: This study represents a first attempt to explore the typology of French female young adults based on personal definitions of healthy eating and to examine inter-group differences regarding their tendencies towards Orthorexia Nervosa (ON), eating disordered (ED) and obsessive-compulsive (OC) behaviors. Method: 362 female adults ( M age = 23.43, SD = 3.82) completed a 40-item questionnaire assessing personal definitions of healthy eating, the Eating Habits Questionnaire, the Eating-Disorders Inventory-3 and the Obsessive-Compulsive Inventory-Revised. Results: Exploratory factor analysis yielded 6 factors for healthy eating definitions: "Health benefits", "Politico-ecological", "Restriction", "Pleasure", "Socio-cultural" and "Dietary avoidance". Cluster analysis based on these factors identified 3 distinct groups: "Self & Environment aware " (SEA), "Restrictive-Avoidant" (RA) and "Sociable-Pleasure seeking" (SP). The SEA cluster emphasized the "Health benefits", "Politico-ecological" and "Dietary avoidance" factors while defining healthy eating. The RA cluster highlighted the "Restriction" and "Dietary avoidance" factors while the SP cluster mainly emphasized the "Pleasure" and "Socio-cultural" factors. Compared to all other clusters, the SEA cluster displayed greater scores in ON behaviors. The RA cluster displayed greater scores in ED behaviors compared to SP cluster. No significant difference was found between clusters regarding OC behaviors. Conclusion: Findings from this study suggest that ON behaviors can vary depending on personal definitions of healthy eating. They further indicate that the definitions of healthy eating related to ON behaviors are largely different from those related to ED and OC behaviors. This study offers considerable support for the possibility of ON being a distinct condition from ED and OC behaviors.